Newspaper digital transformation in Medan: Analysis of SWOT and existence - Rasyid, Abdul (Jurnal Studi Komunikasi, 2022)
The era of digital technology demands adjustments for print mass media entrepreneurs to maintain the continuity of their production and marketing. On the other hand, many people still depend on their interest to continue reading the printed version of the newspaper, given the limitations of internet access and the affordability of using a smartphone. This study aims to determine the existence of newspapers or printed newspapers in the city of Medan and the factors that influence their development and implications for public literacy through printed newspapers. This research method uses qualitative research using a content analysis approach by observing the production figures of printed newspapers, the amount of advertising revenue, and critical analysis of literacy issues. The results showed that the daily printed newspapers in Medan, which amounted to 30 newspapers, were in critical condition and estimated to be closed in 2040. The advertising supply at the heart of newspapers declined drastically to the lowest level. The political economy theory of media put forward by Garnham clearly shows that the mass media, including the printed mass media of newspapers, is closely related to economic problems. This means that the mass media of letters will not be able to live without the support of economic power, and of course, it has implications for the level and quality of literacy of those who read through printed newspapers.